Pioneer Studio / Asrizal Ali…[et al.] - Ali, Asrizal; Mohd Khair, Mohd Haizi; Zulkeply, Mohd Azwar; Ramli, Mohd Hanif; Mansor, Mohd Noor Azlan (2004)
Pioneer Studio is located in Wisma Dato’ Demang Haji Taha, 9289, Jalan Besar Masjid Tanah, 78300, Melaka. This business will be registered on 1 December 2004 and will be start on 1 January 2005... Insya Allah. Our business will focus on musical environment whereby; we’re providing the music studio for all people in our particular area. We’re giving the facilities to our customers who want to enjoy their music and sharp their talent in music arena. Nowadays, as we know that the need of music itself has been one of the necessities in our life. Today, most of people release their tension by listening the music or playing the musical instruments. Sometimes, music can give us inspiration and spirit to work hard. It depends for the individual. Music can be involved the most genre such as metal, punk, ska, grunge, pop rock, balada and so on. Government also had set up many activities in order to attract people especially teenagers to enjoy the music properly. So, it can prevent them from the bad influences like free sex, illegal racing, loiter and so on. So, with believe that by opening the music studio, it also can help the development of music industries in Malaysia, especially in Melaka, we proudly to opening our music studio that called, “PIONEER STUDIO”